2020
DOI: 10.1111/and.13568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the normal sperm morphology rate on the clinical and neonatal outcomes of conventional IVF cycles

Abstract: The present study assessed the influences of the normal sperm morphology rate on the clinical and neonatal outcomes of conventional in vitro fertilisation cycles. This retrospective study analysed 427 and 2,728 cycles from the normal sperm morphology rate <4% and ≥4% group respectively. The clinical (total fertilisation failure, clinical pregnancy, implantation and abortion) and neonatal (sex, gestational age, preterm birth, birthweight, low birth weight, live births and birth defects of newborns) outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Specifically, normal SM < 4% was significantly related to higher rates of total fertilization failure, while clinical pregnancy, implantation, and miscarriage rates did not differ significantly compared to patients with normal SM ≥ 4%. 11 Likewise, lower fertilization and higher total fertilization failure rates in c-IVF cycles were detected in men with isolated teratozoospermia, as compared to those with normal semen profile. 13 Moreover, also sperm concentration, count, and viability could be positively related to enhanced ICSI outcomes.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Specifically, normal SM < 4% was significantly related to higher rates of total fertilization failure, while clinical pregnancy, implantation, and miscarriage rates did not differ significantly compared to patients with normal SM ≥ 4%. 11 Likewise, lower fertilization and higher total fertilization failure rates in c-IVF cycles were detected in men with isolated teratozoospermia, as compared to those with normal semen profile. 13 Moreover, also sperm concentration, count, and viability could be positively related to enhanced ICSI outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, comparing couples which men have normal SM < 4% and those with SM ≥ 4% in in vitro fertilization (IVF) cycles, a significant reduction in fertilization rates was found in the first group, despite the lack of significant differences on clinical and neonatal outcomes 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies (Capelouto et al, 2018; Chen et al, 2020; Grow et al, 1994; Keegan et al, 2007; Kruger et al, 1986; Lundin et al, 1997; Mansour et al, 1995; Mariappen et al, 2018; Mercan et al, 1998; Nagy et al, 1995; Oehninger et al, 1995; Osawa et al, 1999; Schachter‐Safrai et al, 2019) included in the cumulative synthesis reported outcomes on the association of teratozoospermia and pregnancy rates with a reference threshold for teratozoospermia which was 4% in eight studies (Capelouto et al, 2018; Chen et al, 2020; Grow et al, 1994; Mariappen et al, 2018; Mercan et al, 1998; Oehninger et al, 1995; Osawa et al, 1999; Schachter‐Safrai et al, 2019), 5% in three (Keegan et al, 2007; Lundin et al, 1997; Mansour et al, 1995) and 14% in two remaining studies (Kruger et al, 1986; Nagy et al, 1995). Odds ratio estimates ranged from 0.08 to 1.41 with OR <1 indicating lower pregnancy with teratospermia while >1 represents higher odds of pregnancy with teratospermia.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the main findings, patient description and study characteristics of each article. Of the 17 studies included (Kruger et al, 1986;Grow et al, 1994;Nagy et al, 1995;Oehninger et al, 1995;Palermo et al, 1995;Ben-Chetrit et al, 1995;Mansour et al, 1995;Lundin et al, 1997;Mercan et al, 1998;Osawa et al, 1999;Keegan et al, 2007;Dubey et al 2007;Capelouto et al, 2018;Schachter-Safrai et al Mariappen et al, 2018;Chen et al, 2020;Kasman et al, 2021), eight took place within the United States, two in Europe (Belgium and Sweden), one in South Africa, one in Egypt, one in Japan, one in Israel, one in Australia, one in Canada and one in China (Table 1). Four studies investigated only the association of semen parameters and pregnancy rates in IVF.…”
Section: Study Location Types and Sample Size Cohortmentioning
confidence: 99%